East Asian Welfare Regimes 東アジア福祉制度 - Joseph Wong; Andrew DeWit; Ito Peng (Japan Focus)
This chapter by Ito Peng and Joseph Wong on East Asian Asian welfare regimes is very welcome, particularly as a guide for what to watch in our increasingly fluid era of financial, energy and other shocks to the developed and developing economies. The authors review the literature on East Asian welfare states and show how much of it has been concerned with highlighting essential differences between the region and a generalized model of what we see in North America, Europe, and Scandinavia. (We might add that generalizing among those latter cases also seems unwise). One of the critically distinctive features of the East Asian welfare state typology was and remains the rather restricted fiscal role of the state. As the authors point out, in 2005 Japan led East Asia with 18.6% of GDP devoted to social spending. But the average in the OECD and EU countries was, respectively, 20.5 and 27%. Taiwan and Hong Kong are even further removed from the OECD pattern. During the mid-2000s they were only spending about 10% of GDP on social outlays. And then there is Korea, China, and Singapore weighing in with less than 7% of GDP spent on social outlays. The issues are particularly fascinating in light of the literature on the developmental state, pioneered by the late Chalmers Johnson, which highlights each of these countries as examples of state intervention in charting economic development.The “East Asian exceptionalism” literature has generally explained these low levels of explicit state support for welfare through culture, politics, and “productivism.” Confucian values were held to place the locus of social security in the family rather than the state. On top of that, the minimal role of leftist parties and their associated supports (such as trade unions) held back the construction of a full-fledged formation of the welfare state. At the same time, a focus on spurring economic development saw social policy subordinated to a larger productivist emphasis on fostering human capital while protecting the prerogatives of capital over labor.The authors draw insights from these lines of analysis, but view the region itself as a place of diversity. This is most welcome. Even though the region as a whole features a somewhat more restricted role for social spending by the state, the above numbers alone show the enormous differences among the major states within East Asia. A closer look at these countries is especially important since East Asia is now the locus of global growth (Japan aside).Peng and Wong show that there are two very distinct lines of social policy development evident in the region. Japan, South Korea and Taiwan have been evolving inclusive social insurance schemes that are driven by politics, nationalism and demographic challenges and strive to reinforce social solidarity, universality and redistribution. By contrast, China, Singapore and Hong Kong have much more individual-focused, market-based policy regimes. These latter countries are adopting this rather counterintuitive (considering the “Asian values” culturalist emphasis on communitarianism in East Asia) approach due to restricted fiscal capacity in the central state and the lack of credibility for communitarian ideology in what are highly diverse polities.All the countries in East Asia confront rapid ageing as well as the challenge from cheap labor in the other developing countries. The pressure is also being ramped up by the apparently inexorable post-peak oil rise in conventional energy and other resource costs, not to mention the increasingly unstable US dollar-based global financial architecture. And Japan’s unparalleled public sector debt-dependent model of offering seemingly endless life-support for vested interests seems to warrant a special category of its own. But overall, this snapshot of diverse policy evolution within the region is as useful as a Google map for looking at these countries as they seek to grow out of the vulnerability of export dependence and towards more robust and sustainable domestic consumption.